The Efektivitas Love Language dalam Meningkatkan Kepuasan Pernikahan: Systematic Literature Review - Magfiroh, Norma Hasanatul; Sa'diyah, Elok Halimatus; Muallifah, Muallifah (CV. Lentera Literasi Indonesia, 2025)
Love language is becoming increasingly relevant in efforts to improve family satisfaction, especially in strengthening communication between family members in the midst of increasing divorce rates. Given that understanding and applying love language can strengthen relationships, this study explores the effectiveness of love language in the family context as an effort to create a more harmonious environment. Using a Systematic Literature Review (SLR) approach, this article identifies and analyzes empirical studies from various journals and academic sources published between 2013 and 2023. The 12 journals used are both national and international journals. This study aims to assess the extent to which the application of love language affects family satisfaction, as well as the factors that can affect its effectiveness. The results showed that understanding love language preferences among family members can improve communication and reduce conflict, which in turn strengthens relationship satisfaction. However, its effectiveness varies based on cultural, socioeconomic and age differences. This study suggests the need for a more diverse approach in applying love language to achieve optimal results in various family contexts.